Characterization of amplification core and esterase B1 gene responsible for insecticide resistance in Culex. - Mouches, C (1990)
Organophosphorus insecticide (OP) resistance in several Culex species is associated with increased esterase activity resulting from amplification of the corresponding structural gene. In Culex pipiens quinquefasciatus, high levels of OP resistance (approximately 800 times) are due to the esterase B1 gene, which is amplified at least 250-fold. This gene has now been sequenced, and the structure of the amplification unit (amplicon) encompassing the structural gene has been partially characterized. The inferred amino acid sequence of the enzyme revealed regions of strong homology with other eukaryotic serine-esterases, such as cholinesterases, which are the target of OPs. The amplicon covers at least 30 kilobases and contains a constant and highly conserved "core" of 25 kilobases. This core carries a single copy of the esterase gene (2.8 kilobases) as well as other sequences that are present as single or low number copies in the genomes of mosquitoes lacking overproduction of the esterase B1 protein. In the amplicon, the esterase gene is framed by two DNA sequences that are repeated in other parts of the genome of resistant mosquitoes and found in the genome of susceptible mosquitoes but not near the esterase B1 gene. It is suggested that these repetitive sequences may have a role in the amplification process.